보리호위축병 저항성 내도복 다수성 쌀보리 ‘호강’ - 김양길(Yang-Kil Kim); 윤영미(Young-Mi Yoon); 이미자(Mi-Ja Lee); 김경호(Kyong-Ho Kim); 강천식(Chon-Sik Kang); 정영근(Young-Keun Cheong); 박태일(Tae-il Park); 김보경(Bo-Kyeong Kim); 오세관(Sea-kwan Oh); 박종호(Jong-Ho Park) (Korean journal of breeding, 2019)
As a result of the efforts to breed a high yield naked barley cultivar with disease and stress tolerance in response to climate change and proper double cropping of barley and rice in a paddy field. A new naked barley cultivar named ‘Hogang’ was developed from the cross between ‘Suyoung’ and ‘Geukjosuk 55’ at the National Institute of Crop Science, RDA, Korea, in 2016. ‘Hogang’ is a naked barley cultivar used for powdering and mixing with rice. It has good cooking quality, high whiteness, water absorption rate, and expansion rate. Among other quality characteristics, β-glucan content (5.5%) was higher than that of ‘Saessalbori’ cultivar, while the amylose content (21.7%) was lower than that of ‘Saessalbori’. ‘Hogang’ has a short culm length of 69 cm and it is resistant to BaYMV as well as lodging-resistant. As in ‘Saessalbori’, the maturity date of ‘Hogang’ is May 26th. It has large seed size and grain weight of 34.6 g per 1,000 grains. The yield potential of ‘Hogang’ was 4.56 MT/ha, which was 7% higher than that of ‘Saessalbori’. ‘Hogang’ is expected to spread in BaYMV-prone areas since it is a stable and resistant cultivar. (Registration No. 7375) KCI Citation Count: 0